Pengaruh Tata Ruang Kantor dan Semangat Kerja Terhadap Efektivitas Kerja Pegawai di Kantor Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Karanganyar - Anastasia Bunga Kusumaningtyas; Cicilia Dyah Sulistyaningrum Indrawati; Hery Sawiji (Politeknik Kampar, 2024)
This research aims to determine (1) whether there is an influence of office layout on employee work effectiveness at the DPMPTSP Office of Karanganyar Regency, (2) whether there is an influence of work spirit on employee work effectiveness at the DPMPTSP Office of Karanganyar Regency, and (3) whether there is a combined influence of office layout and work spirit on employee work effectiveness at the DPMPTSP Office of Karanganyar Regency. This research is quantitative in nature and employs the correlational method. The population of this study consists of all employees of the DPMPTSP Office of Karanganyar Regency, totaling 50 individuals. The sampling technique used in this study is saturation sampling. Data collection is conducted through the distribution of questionnaires with Likert-scale responses. The validity of the data is tested using Pearson's product-moment correlation, while reliability is assessed using Cronbach's alpha. Data analysis is performed using multiple regression analysis technique with the assistance of SPSS version 26. The research results indicate that 1) there is a positive and significant influence of office layout on employee work effectiveness. This is evidenced by the computed t-value being greater than the tabulated t-value (3,679 > 2,011) and a significance value (0,001 < 0,050), so it can be interpreted that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted, 2) there is a positive and significant influence of work spirit on employee work effectiveness. This is evidenced by the computed t-value being greater than the tabulated t-value (2,215 > 2,011) and a significance value (0,032 < 0,050), so it can be interpreted that H0 is rejected and H2 is accepted, and 3) there is a positive and significant combined influence of office layout and work spirit on employee work effectiveness. This is evidenced by the computed F-value being greater than the tabulated F-value (36,034 > 3,190) and a significance value (0,000 < 0,050), so it can be interpreted that H0 is rejected and H3 is accepted. The results of the multiple linear regression analysis reveal ? = 38,579+0,409X1 + 0,259X2, and the coefficient of determination (R2) is 58,8%, which means that office layout and work spirit together influence work effectiveness by 58,8%, while the remaining 41,2% is influenced by other unexplained variables in this study. Thus, it can be concluded that the overall analysis results support the hypotheses proposed in this research.